Mapping the social-ecological suitability of agroforestry in the US Midwest - Sarah E Castle; Daniel C Miller; Chloe B Wardropper (Environmental Research Letters)
Agroforestry practices offer the potential to increase agricultural sustainability, but their adoption remains limited, especially in some of the world’s most highly productive regions like the United States (US) Midwest. Integrated assessment of the environmental, social, and economic factors that determine agroforestry’s potential benefits and social acceptability is needed to effectively target agroforestry expansion. To meet this need, we used geospatial multi-criteria decision analysis to map agroforestry’s suitability across the US Midwest. We mapped priority areas where agroforestry is expected to reduce the risk of environmental degradation, provide productive tree growth, and be socially and economically viable. We show that integrating social and economic factors dramatically shifted priorities compared to an environmental-only suitability assessment. Using COMET-Planner, we estimated that expanding agroforestry to the top 5% most suitable land from our analysis (totaling 18.3 million acres) has the potential to store 43 [29–58] Mt of CO _2 e per year over the business-as-usual scenario. Our integrated approach can help stakeholders identify target areas for agroforestry and provides a theoretical foundation for interdisciplinary suitability mapping that can be adapted for use in other global regions.